ENTERING IN THE GLOBAL MANUFACTURING OUTSOURCING MARKET AND INNOVATIVE DEVELOPMENT OF THE UKRAINIAN INDUSTRIAL ENTERPRISES - GOROVA, Kseniia; DLUHOPOLSKYI, Oleksandr; DLUHOPOLSKA, Tetiana (Economy and Sociology, 2021)
The urgency of the research is caused by the problem of innovative development that is acutely facing the Ukrainian industrial enterprises. According to statistics, a rather small share of industrial enterprises innovates in their activities and produces innovative products caused by the lack of investment and experience to intensify innovation. Therefore, enterprises should use modern forms of business organization such as outsourcing that has proved itself as a strategic partnership form and a mechanism for the transfer of innovation. The purpose of the research is to develop recommendations for the release of the Ukrainian industrial enterprises to the global manufacturing outsourcing market to ensure their innovative development. The subjects of the study are the types of manufacturing outsourcing and the mechanism of their impact on the innovative development of enterprises. This article is based on the research results of the Ukrainian and foreign scientists, the information on analytical reports, official statistics and public companies’ information. The methods used in the research are analysis and synthesis, theoretical generalization, statistical analysis. The article analyzes the position of Ukraine in the global manufacturing outsourcing market. The prospects of the Ukrainian industrial enterprises to enter the global market of industrial outsourcing have been determined. Recommendations on the choice of type of industrial outsourcing have been developed. The results of the research can be used in the practical activity of industrial enterprises and in further researches in the field of innovation management and enterprise organization.